1880-1900 the nineteenth century - Zdrok-Ptasz, Jodie (San Diego : Greenhaven, 2004)
Describes major world events, including the assassination of president James Garfield, the formation of the Triple Alliance, and the partitioning of Africa, through both primary and secondary documents.
Includes bibliographical references and index
Keywords: Hitler, Adolf -- 1889-1945.; World politics -- To 1900.; Technological innovations; Inventions; China -- History -- Boxer Rebellion, 1899-1901.